Legal operations in a global context - Khomiakov, Dmytro (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
Background. The emergence of the concept of warfare, defined as the use of law to wage war, has prompted a reassessment of the strength of the international order based on the rule of law. Similar to the regulation of cyberspace, information threats, and instruments of economic and financial pressure, warfare is a non-kinetic action that does not follow the traditional course of an armed attack. Caught off guard, states do not knowhow to respond to these non-kinetic actions as they take place in a new and rapidly changing regulatory environment.Methods. The source base of the study is formed by documents of international organizations and scientific publications on legal operations. The author uses the dialectical, historical, comparative legal methods to track the transformation of views on the processes of planning and conducting legal operations; systemic and structural, formal and logical methods to determine the provisions which should be taken into account in the process of introducing the concepts of legal operations into the activities of the Armed Forces of Ukraine; and methods of analysis, generalization and synthesis to develop relevant proposals.Results. International official documents (agreements, protocols, conventions, recommendations, standards, declarations, communiqués, messages, charters) that regulate and govern the issue of hybrid warfare were summarized and systematized; Proposals for the implementation of legal operations concepts in Ukraine were developed.Conclusions. The results of this study develop the ideas of other researchers on the expediency of introducing the concept and implementation of legal operations in the context of hybrid warfare.
Keywords: legal operations, hybrid warfare, legal norms, strategic goals